Effects of the mu-opioid receptor agonist morphine on facial mimicry and emotion recognition. (August 2022) - Massaccesi, Claudia; Korb, Sebastian; Willeit, Matthaeus; Quednow, Boris B.; Silani, Giorgia
Abstract: Facial mimicry and emotion recognition are two socio-cognitive abilities involved in adaptive socio-emotional behavior, promoting affiliation and the establishment of social bonds. The mu-opioid receptor (MOR) system plays a key role in affiliation and social bonding. However, it remains unclear whether MORs are involved in the categorization and spontaneous mimicry of emotional facial expressions. Using a randomized, placebo-controlled, double-blind, between-subjects design, we investigated in 82 healthy female volunteers the effects of the specific MOR agonist morphine on the recognition accuracy of emotional faces (happiness, anger, fear), and on their facial mimicry (measured with electromyography). Frequentist statistics did not reveal any significant effects of drug administration on facial mimicry or emotion recognition abilities. However, post hoc Bayesian analyses provided support for an effect of morphine on facial mimicry of fearful facial expressions. Specifically, compared to placebo, morphine reduced mimicry of fear, as shown by lower activity of the frontalis muscle. Bayesian analyses also provided support for the absence of a drug effect on mimicry of happy and angry facial expressions, which were assessed with the zygomaticus major and corrugator supercilii muscles, as well as on emotion recognition accuracy. These findings suggest that MOR activity is involved in automatic facial responses to fearful stimuli, but not in their identification. Overall, the current results, together with the previously reported small effects of opioid compounds, suggest a relatively marginal role of the MOR system in emotion simulation and perception. Highlights: We investigated the effects of morphine on facial mimicry and emotion recognition. Morphine reduced fear mimicry. Morphine had no significant effects on recognition of happiness, fear, and anger.